Clinico¬pathological features and phylogenetic analysis of rabies infection in local Iraqi breed cattle - M. H. Hussain; Kh. A. Mansour; S. A. A. Al-Redah; A. J. Abid (Bulgarian Journal of Veterinary Medicine)
Rabies is a lethal viral disease with no specific treatment caused by the Lyssavirus, which renders it dangerously hostile towards cattle. This study was conducted to score clinical and pathologic criteria for rabid dogs in the middle Euphrates of Iraq and link them to phylogenetic analysis. Eighty-one cattle were suspected to have rabies after a history of being attacked and having signs of rabies: rest-lessness, aggression, drooling saliva, hitting head to fences, inappetence, recurrent failed trials of defecation with an opened anus, and fever. Samples of the dead cattle cerebellum were referred for histopathology and molecular detection to confirm the diagnosis. The study showed that the most common clinical signs in the affected animals were behavioural changes (30% of all cattle), followed by a fever (25%), and ataxia (16%). The rest of the clinical signs appeared in varying proportions. With regard to histopathological evaluation, neurological lesions, inflammation, and gliosis scored 3 and were described as severe lesions, while the Negri bodies were moderately scored by 2 as an aver-age number. The phylogenetic analysis revealed variations at a total of 24 places in multiple sequence alignments between two field rabies virus nucleotide sequences from the current investigation (>MW893685 and >MW893684) and 48 GenBank nucleotide sequences, including the reference strain (>NC_001542). Significant differences in relative locations were found between several field isolates and reference strains. Our study showed substitutions of phenylalanine, proline, histidine, lysine, serine and proline, threonine, and asparagine to serine, glutamine, arginine, leucine, serine, threonine, methionine, and valine at different sites. Furthermore, when building the phylogenetic tree, the current study isolates (Iraqi isolates) were mostly similar to Nigerian isolates. In conclusion, rabies in cattle is an endemic, life-threatening, transboundary disease that affects animals and public health in Iraq and needs more studies to explain the cause behind the recorded substitution mutations and the similarity of the Iraqi isolates with Nigerian isolates.